Critical Thinking in Geometry: An Analysis of Eighth-Graders Solving Quadrilateral Problems - Fitriyani, Cantika; Khoirunissa, Khoirunissa; Pujianti, Amelia (Papanda Publisher, 2024)
This study investigates the critical thinking skills of eighth-grade students in solving quadrilateral problems in mathematics. A qualitative descriptive approach was employed, with three students selected purposively to represent high, medium, and low levels of critical thinking. Data were collected through written tests and semi-structured interviews and analysed using the Miles and Huberman interactive model, which includes data collection, reduction, display, and verification. The findings reveal significant variation in students’ critical thinking abilities. Students with high critical thinking skills demonstrated proficiency in interpretation, analysis, evaluation, and inference, providing accurate solutions to problems and logical conclusions. Medium-level students performed well in interpretation, analysis, and evaluation but partially lacked in inference. Students with low critical thinking skills struggled across all indicators, resulting in incomplete or incorrect solutions to problems. These findings underscore the importance of integrating instructional strategies that promote all dimensions of critical thinking in mathematics learning.